A theory of plant function helps to explain leaf-trait and productivity responses to elevation - Peng,Y; Bloomfield,K; Prentice,IC (New Phytologist, 2020)
Several publications have examined leaftrait and carboncycling shifts along an AmazonAndes transect spanning 3.5 km elevation and 16 mean annual temperature. Photosynthetic capacity was previously shown to increase as temperature declines with increasing elevation, counteracting enzymekinetic effects. Primary production declines, nonetheless, due to decreasing light availability. We aimed to predict leaftrait and production gradients from first principles, using published data to test an emerging theory whereby photosynthetic traits and primary production depend on optimal acclimation and/or adaptation to environment.We reanalysed published data for 210 species at 25 sites, fitting linear relationships to elevation for both predicted and observed photosynthetic traits and primary production.Declining leafinternal/ambient CO2 ratio (χ) and increasing carboxylation (Vcmax) and electrontransport (Jmax) capacities with increasing elevation were predicted. Increases in leaf nitrogen content with elevation were explained by increasing Vcmax and leaf massperarea. Leaf and soil phosphorus covaried, but after controlling for elevation, no nutrient metric accounted for any additional variance in photosynthetic traits. Primary production was predicted to decline with elevation.This analysis unifies leaf and ecosystem observations in a common theoretical framework. The insensitivity of primary production to temperature is shown to emerge as a consequence of the optimization of photosynthetic traits.